Quimioterapia Adjuvante no Câncer da Mama - Broecker Neto, Adalberto (2023)
A retrospectiva analysis of adjuvant chemotherapy in 95 patients with breast cancer was carried out. Patient stratification was made according to pathological status of axilary lymphonodes: group A patients with 1-3 positive nodes and group B patients with more than 3 positive lymphnodes. At sixty months the probability of survival was 86.1% for group A and 83% for group B (p=0.042) and, probability of disease free survival was 86.1%> in group A and 64.4% in group B (p<0.001). Forty nine patients were foilowed for at least 2 years and analysis after 24 months showed survival of 95.4% for group A and 85,1% for B (p=0.014) and, survival free of disease of 86.3% in group A and 66,6% in group B (p =0.415). Recurrence rate was 23.4% for patients receiving 85%> or more of programmed dose and 45% for patients whith lower doses. Local recurrences were identical for patients with or without radiotherapy. A comparison with the Milan study was made.